1990
DOI: 10.1007/bf00563782
|View full text |Cite
|
Sign up to set email alerts
|

High cell density suspension culture of mammalian anchorage independent cells: Oxygen transfer by gas sparging and defoaming with a hydrophobic net

Abstract: Gas sparging directly into the culture-broth is not done in cell culture, except when the gas flow rate is very small, because much foaming occurs. During screening of defoaming methods, foam was observed to be broken up effectively when it made contact with a net fabricated from hydrophobic materials. Providing a highly efficient oxygen supply to suspension culture was tried using the new defoaming method. In a 5 l reactor equipped with the foam-eliminating net fabricated with polysiloxane, oxygen was transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Himmelfarb et al (1969), for instance, applied a spin filter for retention of murine leukemia suspension cells. Butler et al (1983) used a column separator for retention of Madin–Darby canine kidney (MDCK) cells immobilized on positively charged microcarriers (MCs), and Ishida et al (1990) tested a hydrophobic hollow fiber membrane for retention of mouse hybridoma cells and rat ascites hepatoma cells in a long‐term application. Additional techniques were described by Voisard et al (2003), Shirgaonkar et al (2004), and Castilho and Medronho (2002).…”
Section: Introductionmentioning
confidence: 99%
“…Himmelfarb et al (1969), for instance, applied a spin filter for retention of murine leukemia suspension cells. Butler et al (1983) used a column separator for retention of Madin–Darby canine kidney (MDCK) cells immobilized on positively charged microcarriers (MCs), and Ishida et al (1990) tested a hydrophobic hollow fiber membrane for retention of mouse hybridoma cells and rat ascites hepatoma cells in a long‐term application. Additional techniques were described by Voisard et al (2003), Shirgaonkar et al (2004), and Castilho and Medronho (2002).…”
Section: Introductionmentioning
confidence: 99%
“…The various process parameters and ingredients that influence the AVMs and AVM B1a production of the original strain have been extensively described in the literature [ 16 20 ]. Furthermore, many studies have shown that the DO, the oxygen supply, and the agitation speed are interrelated in varied culture conditions [ 21 23 ]; decoupling of these factors is often obtained by adjustment of the stirred-tank bioreactor stir speed, the type and number of stirred-tank bioreactors, the gas flow rate, cell growth, and the morphology of mycelia; metabolite biosynthesis variably depends on these factors [ 24 26 ]. Because the DO was found to be the primary factor affecting microbial metabolite production, most culture processes adopt a DO-control strategy by adjusting agitation.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a debate on whether acrylamide particle can penetrate into the globular fold of the folded protein molecules or not (Strambini and Gonnelli 2010). Recent studies demonstrate that proteins will have thick ensembles of secondary and tertiary structures even after denaturation with detergents and chaotropic agents such as SDS and urea (Parker and Song 1992;Itri et al 2004 and subsequently dissolves the protein molecules in the aqueous medium (Ishida et al 1990;Valstar et al 2000;La Mesa 2005). The most studied and suitable surfactants for applications in one and two-dimensional polyacrylamide gel electrophoresis are SDS and CHAPS, where the former is an anionic detergent and the latter is zwitterionic detergent.…”
mentioning
confidence: 99%